Scientific statement on the coverage of bats by the current pesticide risk assessment for birds and mammals. (29th July 2019) - ,; Hernández‐Jerez, Antonio; Adriaanse, Paulien; Aldrich, Annette; Berny, Philippe; Coja, Tamara; Duquesne, Sabine; Gimsing, Anne Louise; Marina, Marinovich; Millet, Maurice; Pelkonen, Olavi; Pieper, Silvia; et al.
Abstract: Bats are an important group of mammals, frequently foraging in farmland and potentially exposed to pesticides. This statement considers whether the current risk assessment performed for birds and ground dwelling mammals exposed to pesticides is also protective of bats. Three main issues were addressed. Firstly, whether bats are toxicologically more or less sensitive than the most sensitive birds and mammals. Secondly, whether oral exposure of bats to pesticides is greater or lower than in ground dwelling mammals and birds. Thirdly, whether there are other important exposure routes relevant to bats. A large variation in toxicological sensitivity and no relationship between sensitivity of bats and bird or mammal test‐species to pesticides could be found. In addition, bats have unique traits, such as echolocation and torpor which can be adversely affected by exposure to pesticides and which are not covered by the endpoints currently selected for wild mammal risk assessment. The current exposure assessment methodology was used for oral exposure and adapted to bats using bat‐specific parameters. For oral exposure, it was concluded that for most standard risk assessment scenarios the current approach did not cover exposure of bats to pesticide residues in food. Calculations of potential dermal exposure for bats foraging during spraying operations suggest that this may be a very important exposure route. Dermal routes of exposure should be combined with inhalation and oral exposure. Based on the evidence compiled, the Panel concludes that bats are not adequately covered by the current risk assessment approach, and that there is a need to develop a bat‐specific risk assessment scheme. In general, there was scarcity of data to assess the risks for bat exposed to pesticides. Recommendations for research are made, including identification of alternatives to laboratory testing of bats to assess toxicological effects.